Assessment in Early Childhood Education: The Importance of Monitoring Children's Development - Zannah, Raudatul; Rahmadani, Suci; Rukayah, Ity (Universitas PGRI Sumatera Barat, 2024)
Assessment in early childhood education (ECED) plays a crucial role in identifying and facilitating children's development. In the early childhood period, children experience rapid development in physical, social, emotional and cognitive aspects. Therefore, proper assessment aims not only to provide grades, but also to understand how children learn and interact with their surroundings. There are several types of assessments that are often used, including formative assessments that are conducted continuously throughout the learning process, and summative assessments that are conducted at the end of a period. Performance and portfolio assessments are also effective methods of assessing children's progress. Through comprehensive assessments, educators can understand the specific needs of each child, design appropriate learning experiences and involve parents in the learning process. Results from assessments provide valuable information that can be used to adjust the curriculum, improve teaching methods and create a better learning environment. Thus, assessment becomes an important tool in supporting children's optimal development in the early years. In this study, we emphasis the importance of implementing child-centred assessments and collaboration between educators and parents in evaluating and strengthening children's learning experiences. With the right approach, assessment can not only improve children's learning outcomes, but also strengthen their foundation for future learning.